(3eONd Edi GdEbJUGO GdQjGVj (B/s - (3ZQS GdOjf, eMeOs; (3jGSQ, eMeO LGO Gddgs ([(3Ohf ecGf(B]: s (3eWHYI GdESQGA(B, s, 2004)
(3Cge GdCOhGJ GdQjGVjI GdeSJNOeI aj GdJMdjd GdEbJUGOj,GdeYGOdGJ hGdOhGd hGdXhGgQ GdEbJUGOjI,GdhVY GdCeKd,GdHQeLI GdNWjI hHYV GdJWHjbGJ GdEbJUGOjI,fXQjI GdeHGQjGJ,eSGFd aj GdEbJUGO GdQjGVjs
(3HHdhZQGajG(B: (3U(B.255s
Keywords: (3GdGbJUGO GdQjGVjs